2013
DOI: 10.1590/s1516-05722013000500017
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e atividade inseticida do óleo essencial de Schinus terebinthifolius Raddi (Anacardiaceae) sobre a broca-do-café (Hypothenemus hampei) Ferrari

Abstract: RESUMO:O óleo essencial das folhas de Schinus terebinthifolius foi obtido por hidrodestilação e analisado por CG-EM. O rendimento do óleo foi de 0,8%, sendo identificados 37 constituintes químicos. Os componentes principais foram germacreno D (25,0%), (E)-b-cariofileno (17,5%) e d-elemeno (10,5%). O óleo essencial foi diluído em acetona nas concentrações de 10 -2 a 10 -8 e aplicado aos insetos (Hypothenemus hampei) por aplicação tópica e exposição em superfície contaminada. As taxas de mortalidade foram avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 7 publications
(5 reference statements)
2
21
0
8
Order By: Relevance
“…The insecticide effect promoted by S. terebinthifolius may be related to the chemical structure of compounds present in extracts from its leaves. Santos et al (2013) identified the presence of phenolic substances, such as flavonoids from the aqueous extract and ethyl acetate from the leaves of S. terebinthifolius. Whereas Guimarães et al (2014), evaluating the repellant, insecticide and fago inhibitor effect of the extracts of pepper dedo-de-moça (Capsicum baccatum) over corn Sitophilus zeamais weevil, found that the aqueous extract of seeds of pepper dedo-de-moça was the one that presented the greatest potential insecticide compared to the alcoholic extracts of 2.5, 5 and 10%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insecticide effect promoted by S. terebinthifolius may be related to the chemical structure of compounds present in extracts from its leaves. Santos et al (2013) identified the presence of phenolic substances, such as flavonoids from the aqueous extract and ethyl acetate from the leaves of S. terebinthifolius. Whereas Guimarães et al (2014), evaluating the repellant, insecticide and fago inhibitor effect of the extracts of pepper dedo-de-moça (Capsicum baccatum) over corn Sitophilus zeamais weevil, found that the aqueous extract of seeds of pepper dedo-de-moça was the one that presented the greatest potential insecticide compared to the alcoholic extracts of 2.5, 5 and 10%.…”
Section: Resultsmentioning
confidence: 99%
“…Since they are obtained from renewable resources, they are rapidly degradable, act without leaving residues in food, do not damage the ecosystem and are less toxic to humans (Olivo et al, 2008;Agnolin et al, 2010). The Brazilian pepper tree (Schinus terebinthifolius) has been widely studied and its extracts fight against insect pests (Santos et al, 2007a(Santos et al, , 2013. This is due to the chemical constituents distributed in plants' parts, such as tannin, bioflavonoids, triterpernic acids, mono and sesquiterpenes present in leaves (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hypothenemus hampei Ferrari (Coleoptera, Scolytidae) has been controlled using Schinus terebinthifolius essential oil (Santos et al 2013) and Zabrotes subfaciatus Boheman (Coleoptera: Bruchidae) using Laurus nobilis essential oils (Silva et al 2013). Moreover, due to the fact that essential oils are composed of different substances, they can be important tools for insect resistance management, since these compounds may act on different physiological routes of the insect (Bakkali et al 2008, Regnault-Roger et al 2012.…”
Section: Key-wordsmentioning
confidence: 99%
“…Além destes, também foram observados α-pineno (Matsuo et al, 2011) e limoneno (Santos et al, 2007). Estudos recentes comprovaram atividade antimicrobiana (Degáspari et al, 2005;Johann et al, 2008;Paiva et al, 2010;Machado et al, 2012;Gomes et al, 2013), antiinflamatória (Medeiros et al, 2007;Varela-Barca et al, 2007), antifúngica (Fenner et al, 2006;Santos et al, 2010;Khan, 2013), antitumoral (Queires et al, 2013) e inseticida (Santos et al, 2013) dessa espécie.…”
Section: Introductionunclassified